Single-dose pharmacokinetics, safety, and tolerability of the dual endothelin receptor antagonist aprocitentan in subjects with moderate hepatic impairment - Fontes, Magda S. C.; Dingemanse, Jasper; Halabi, Atef; Tomaszewska-Kiecana, Monika; Sidharta, Patricia N. (Scientific reports, 2022)
The effect of moderate hepatic impairment on the pharmacokinetics (PK), safety, and tolerability of the dual endothelin receptor antagonist aprocitentan was clinically investigated as 25% of aprocitentan is cleared through the liver. Aprocitentan is in clinical development for the treatment of resistant hypertension. This was an open-label, Phase 1 study. Subjects were recruited in two groups (i.e., moderate hepatic impairment (Child–Pugh B; n = 8) and matched healthy subjects (n = 9) and received a single oral dose of 25 mg aprocitentan. Thereafter, they were observed for 14 days. Due to personal reasons one healthy subject discontinued the study. The PK of aprocitentan were similar between subjects with moderate hepatic impairment and healthy subjects, with maximum plasma concentrations (C max ) reached at 4.0 h. There was no difference in C max , indicated by the geometric means ratio (90% confidence interval) of 1.03 (0.86–1.24). There was a lower apparent clearance, a similar apparent volume of distribution, a longer terminal half-life (56.4 h vs 48.3 h in healthy subjects), and an increase in area under the curve from zero to infinity of 23% in moderate hepatically impaired subjects compared to healthy subjects. There were no differences observed in plasma protein binding (range 98.7–99.0%). Aprocitentan was well tolerated, and headache was the only adverse event reported by one subject. In conclusion, there were no clinically relevant differences in PK between subjects with moderate hepatic impairment and healthy subjects. Based on these results, aprocitentan can be administered in subjects with mild and moderate hepatic impairment and dose adjustment is not required. Clinical Trial Registration ClinicalTrials.gov NCT04252495.